Tribological and thermal characteristics of an epoxy-based composite containing polyaryletherketone. (May 2022) - Hu, Haixia; Shu, Rui; Meng, Limin; Yu, Tiansheng; Wang, Chengjun; Chen, Dingming; Shen, Yuzhe
Current research work focuses on the tribological and thermal properties of epoxy resin matrix composites, which were modified by polyaryletherketone (PAEK-C). The results of the infrared spectra and morphologies of fracture surfaces experiments corroborate the successful synthesis of the materials. From the tribological experiments, it can be known that when the mass fraction of PAEK-C was 10 phr., the corresponding composite exhibited the outstanding wear performances, which could be ascribed to the higher H/E ratio. Based on the results of tribological experiments, it could be obtained that the main wear mechanism is governed by combination of the plastic deformation, creation of vertical cracks in the sliding track, separation of debris, and material waves due to adhesions. In addition, the glass transition temperatures ( T g ) and heat-resistance index ( T HRI ) of the PAEK-C/epoxy resin higher than those of pure epoxy resin matrix, respectively. Furthermore, when the mass fraction of PAEK-C increased, the heat resistance index ( T HRI ) of the corresponding composite is 196.3°C, which is higher than that of neat epoxy resin (180.9°C). Also, according to the results of thermogravimetric analysis experiments, it could conclude that the activation energy of the curing process is situated in the range of 150–160 kJ mol −1 depending on the mass fraction of epoxy resins.